Olanzapine induced neuroleptic malignant syndrome - Patra, Bichitra Nanda (Medknow Publications & Media Pvt Ltd, 2013)
An 18 year old male diagnosed as a case of bipolar affective disorder (BPAD), developed neuroleptic malignant syndrome (NMS) following treatment with olanzapine (20 mg per day), an atypical antipsychotic drug. NMS is usually seen with typical antipsychotic drugs. The patient was diagnosed as a case of NMS, offending agent was immediately withdrawn and prompt treatment with bromocriptine and levodopa produced a good recovery. The various features of the case are discussed in view of the potential mortality of the syndrome.